2020
DOI: 10.1155/2020/8876394
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lb. plantarum BFE 5092 Fermentation on Antinutrient and Oligosaccharide Composition of Whole Red Haricot Bean (Phaseolus vulgaris L)

Abstract: Common beans are a leguminous plant of the genus Phaseolus. They are rich in protein, energy, and minerals. They confer a wide range of health benefits when consumed. Utilization of common bean has however been poor due to high antinutrient content that results in reduced nutrient digestibility and mineral bioavailability. Flatulence after consumption is also a huge deterrent to common bean consumption. Lactic acid fermentation is the most common form of food fermentation with the Lactobacilli spp dominating m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…In agreement, the literature reports that the species Lb. plantarum was found to be effective in reducing RFOs when applied to ferment whole red haricot [ 36 ] and chickpea flours [ 37 ]. An increment in essential amino acids in fermented bean flours ( Phaseolus vulgaris ) was also observed when fermented by other types of microorganisms, such as Pleurotus ostreatus [ 38 ] and Aspergillus oryzae [ 39 ] fungi.…”
Section: Resultsmentioning
confidence: 99%
“…In agreement, the literature reports that the species Lb. plantarum was found to be effective in reducing RFOs when applied to ferment whole red haricot [ 36 ] and chickpea flours [ 37 ]. An increment in essential amino acids in fermented bean flours ( Phaseolus vulgaris ) was also observed when fermented by other types of microorganisms, such as Pleurotus ostreatus [ 38 ] and Aspergillus oryzae [ 39 ] fungi.…”
Section: Resultsmentioning
confidence: 99%
“…Ogodo et al (2019) found that LAB fermentation of maize flour decreased the levels of antinutritional factors more significantly than spontaneous fermentation. However, in another study, a different result was obtained whereby the tannin and phytate contents in Phaseolus vulgaris L. showed a larger reduction when spontaneous fermentation was applied, as compared to fermentation with Lactobacillus plantarum BFE 5092 (Kitum et al, 2020). Therefore, the reduction of antinutrient concentration is likely to be dependent on the type of food, rather than the species of the microflora.…”
Section: Application Of Fermentation To Reduce Antinutrients In Plant...mentioning
confidence: 94%
“…Fermentation of food is an anaerobic process that involves the chemical conversion of carbohydrates into lower molecular weight compounds through the help of microorganisms such as bacteria, yeasts, moulds, or combination of these (Vuppala and Murthy, 2015). In Table 2, many studies have proven that fermentation is an effective method to reduce antinutrient levels in foods (Sharma et al, 2015;Olagunju et al, 2018;Kitum et al, 2020). In foods, lactic acid bacteria (LAB) are the most common microorganisms used or present during fermentation.…”
Section: Application Of Fermentation To Reduce Antinutrients In Plant...mentioning
confidence: 99%
“…plantarum ). Fermentation was carried out by taking fresh leaves of B. campestris from each stage [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…After every 6 h, 5 mL of the fermentation solution was aseptically removed to measure the pH with a pH meter (Model: ST3100 OHAUS corporation, Parsippany, NJ, USA) [ 13 ]. Acidity was calculated by diluting 10 mL of fermentation solution with 50 mL of water and titrating to pH 8.00 with 0.1 N NaOH.…”
Section: Methodsmentioning
confidence: 99%